Naïve rat umbilical cord matrix stem cells significantly attenuate mammary tumor growth through modulation of endogenous immune responses - Kawabata, Atsushi; Ohta, Naomi; Seiler, Garret; Pyle, Marla M.; Ishiguro, Susumu; Zhang, Yongqing; Becker, Kevin G.; Troyer, Deryl L.; Tamura, Masaaki (My University, 2013)
Background: Un-engineered human and rat umbilical cord matrix stem cells (rUCMSC) attenuate growth of several types of tumors in mice and rats. However, the mechanism by which UCMSC attenuate tumor growth has not been studied rigorously. Methods- The possible mechanisms of tumor growth attenuation by rUCMSC were studied using orthotopic Mat B III rat mammary tumor grafts in female F344 rats. Tumor-infiltrating leukocytes were identified and quantified by immunohistochemical image analysis. Potential cytokines involved in lymphocyte infiltration in the tumors were determined by microarray and Western blot analysis. The Boyden chamber migration assay was performed for the functional analysis of identified cytokines. Results: rUCMSC markedly attenuated the tumor growth; this attenuation was accompanied by considerable lymphocyte infiltration. Immunohistochemical analysis revealed that the majority of infiltrating lymphocytes in the rUCMSC-treated tumors were CD3+ T cells. In addition, treatment with rUCMSC significantly increased infiltration of CD 8+ and CD4+ T cells and NK cells throughout tumor tissue. CD68+ monocytes/macrophages and FoxP3+ regulatory T cells were scarcely observed, only in the tumors of the PBS control group. Microarray analysis of rUCMSC identified that monocyte chemotactic protein (MCP)-1 is involved in rUCMSCinduced lymphocyte infiltration in the tumor tissues. Discussion: These results suggest that naïve rUCMSC attenuated mammary tumor growth at least in part by enhancing host anti-tumor immune responses. Thus, naïve UCMSC can be used as powerful therapeutic cells for breast cancer treatment, and MCP-1 may be a key molecule to enhance the effect of UCMSC at the tumor site.
Keywords: Rat umbilical cord matrix stem cells; Mammary tumor; Immune response; T cells; Macrophages